Preserving Memory through Media Migration Rare Books in Bogor Botanic Gardens Library for Researcher Community - Adiba, Syifa; Febriyanto, Febriyanto (International Journal of Information Studies, 2025)
This paper is about Bogor Botanic Gardens Library which is one of the oldest libraries in Indonesia. The library collected the rare and old books, containing memory knowledge in botany field which is widely used by researchers. To keep the information contained in the memory for the benefit of knowledge development, librarian conduct preservation by transferring the rare collection media into digital form. Reformatting library material in preservation activity is one of a way to reduce/repair library material. Rare books are library collections that rarely get any attention. Rare books condition that is not maintained well will affect the retrieval information process by the users. The purposes of this article are to explain library materials reformatting activity, especially rare books in Bogor Botanic Gardens Library, alongside with strengthens and weakness. The result from this research then will be linked with library material preservation and retrieval information; in this case, it’s a rare book. Bogor Botanic Gardens is chosen for research object because the library has so many rare books and cannot be found in any other place; also the rare books need special treatment. This research is conducted using observation method with qualitative analysis. At the end of this article, it will afford criticism and suggestion about reformatting process in Bogor Botanic Garden.